2008
DOI: 10.1160/th08-02-0124
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin inhibits tissue factor expression and enhances tissue factor pathway inhibitor expression in human endothelial cells

Abstract: Tissue factor (TF) plays a pivotal role in thrombus formation and atherogenesis in acute coronary syndrome. Tissue factor pathway inhibitor (TFPI) is a specific physiological inhibitor of TF/FVIIa complex that regulates TF-induced coagulation. Adiponectin (Adp) is an adipocyte-specific adipocytokine with anti-atherogenic and anti-diabetic properties. Adp inhibits inflammatory cytokine and adhesion molecules expression, and it can prevent endothelial dysfunction. In this study, we investigated the effects of Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…Intracellular cAMP levels decrease under an oxygen free radical-generating system (Raynaud et al 1997), and cAMP analogs display anti-apoptotic and antioxidant effects (Kim et al 2002, Fujita et al 2006. A substantial body of evidence suggests that adiponectin functions as an activator of cAMP in macrophages (Zhao et al 2005) and endothelial cells (Ouedraogo et al 2006, Chen et al 2008. Moreover, adiponectinmediated activation of cAMP exerts antioxidative effects as well as anti-inflammatory and anti-atherosclerotic effects (Ouchi et al 2000, Zhao et al 2005, Ouedraogo et al 2006, Chen et al 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular cAMP levels decrease under an oxygen free radical-generating system (Raynaud et al 1997), and cAMP analogs display anti-apoptotic and antioxidant effects (Kim et al 2002, Fujita et al 2006. A substantial body of evidence suggests that adiponectin functions as an activator of cAMP in macrophages (Zhao et al 2005) and endothelial cells (Ouedraogo et al 2006, Chen et al 2008. Moreover, adiponectinmediated activation of cAMP exerts antioxidative effects as well as anti-inflammatory and anti-atherosclerotic effects (Ouchi et al 2000, Zhao et al 2005, Ouedraogo et al 2006, Chen et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A substantial body of evidence suggests that adiponectin functions as an activator of cAMP in macrophages (Zhao et al 2005) and endothelial cells (Ouedraogo et al 2006, Chen et al 2008. Moreover, adiponectinmediated activation of cAMP exerts antioxidative effects as well as anti-inflammatory and anti-atherosclerotic effects (Ouchi et al 2000, Zhao et al 2005, Ouedraogo et al 2006, Chen et al 2008). In the current study, adiponectin activated cAMP level in HUVECs, and the beneficial effect of adiponectin was reversed by the inhibitors of cAMP and PKA suggesting that the cAMP/PKA pathway also mediates the antioxidant and anti-apoptotic effects of adiponectin.…”
Section: Discussionmentioning
confidence: 99%
“…35 Conversely, adiponectin inhibits TNF-a-induced TF expression in human endothelial cells through inhibition of NF-kB signaling. 51 …”
Section: Tf Regulation In Obesitymentioning
confidence: 99%
“…In addition, Adp can inhibit endothelial nuclear factor-kappa B (NF-κB) activity stimulated by TNF-α via a cAMP-dependent pathway in human aortic endothelial cells [11]. Furthermore, we previously reported that Adp treatment could inhibit TNF-α-induced NF-kB P65 activity in HUVECs and increase the AMPK phosphorylation level [12]. Therefore, the aim of the present study was to examine whether Adp regulates TNF-α-induced PAI-1 expression via the cAMP-AMPK-NF-k-B signaling pathway.…”
Section: Introductionmentioning
confidence: 99%